Analisis Penyelesaian Sengketa Tentang Batas Tanah Pada Sertifikat Tanah di Kantor Pertanahan Kabupaten Sukoharjo - Jauhara Berliana Aziza Putri; Rahayu Subekti; Purwono Sungkowo Raharjo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Land as a fundamental need for human life, makes humans dependent on the existence of land. An increase in population that is not balanced with the number of deaths will increase the need for shelter. This has an impact on increasing urban development with the establishment of housing and settlements. Difficulties in fulfilling housing cause people to compete to have as much land rights as they want. This causes land disputes between one party and another party because there are parties who feel aggrieved by other parties. This article aims to determine the causes of land boundary disputes in Sukoharjo Regency and efforts to resolve disputes about land boundaries in Sukoharjo Regency. This research is included in empirical legal research and is descriptive which is analyzed qualitatively. The results showed that the cause of the land boundary dispute that occurred in Sukoharjo Regency was misunderstanding, ignorance, and also there was an element of fraud from one party. Efforts to resolve land boundary disputes that occurred in Sukoharjo Regency were resolved by mediation by the National Land Agency of Sukoharjo Regency.